MeCP2 Deficiency in Neuroglia: New Progress in the Pathogenesis of Rett Syndrome - Jin, Xu-Rui; Chen, Xing-Shu; Xiao, Lan (Frontiers in Molecular Neuroscience, 2017)
Rett syndrome (RTT) is an X-linked neurodevelopmental disease predominantly caused by mutations of the methyl-CpG-binding protein 2 (MeCP2) gene. Generally, RTT has been attributed to neuron-centric dysfunction. However, increasing evidence has shown that glial abnormalities are also involved in the pathogenesis of RTT. Mice that are MeCP2-null specifically in glial cells showed similar behavioral and/or neuronal abnormalities as those found in MeCP2-null mice, a mouse model of RTT. MeCP2 deficiency in astrocytes impacts the expression of glial intermediate filament proteins such as fibrillary acidic protein (GFAP) and S100 and induces neuron toxicity by disturbing glutamate metabolism or enhancing microtubule instability. MeCP2 deficiency in oligodendrocytes (OLs) results in down-regulation of myelin gene expression and impacts myelination. While MeCP2-deficient microglia cells fail in response to environmental stimuli, release excessive glutamate, and aggravate impairment of the neuronal circuit. In this review, we mainly focus on the progress in determining the role of MeCP2 in glial cells involved in RTT, which may provide further insight into a therapeutic intervention for RTT.